2021
DOI: 10.1111/ecog.05478
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐taxa colonisation along the foreland of a vanishing equatorial glacier

Abstract: Retreating glaciers, icons of climate change, release new potential habitats for both aquatic and terrestrial organisms. High‐elevation species are threatened by temperature increases and the upward migration of lowlands species. Improving our understanding of successional processes after glacier retreat becomes urgent, especially in the tropics, where glacier shrinkage is particularly fast. We examined the successional patterns of aquatic invertebrates, ground beetles, terrestrial plants, soil eukaryotes (alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 85 publications
5
34
0
2
Order By: Relevance
“…However, in agreement with what has been frequently reported for glacial primary succession (Matthews, 1992;Walker and del Moral, 2003;Pratch and Walker, 2020;Rosero et al, 2021), we found a clear successional increase in superficial SOM and N t . Values were relatively high considering the limiting conditions for soil development in the study area (e.g., steep slopes with hard exposed metamorphic bedrock and low vegetation cover), although they remained below typical values reported in the superpáramo belt in Venezuela between 4,000 and 4,400 m asl (Malagón, 1982;Pérez, 1995).…”
Section: Soil Developmentsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in agreement with what has been frequently reported for glacial primary succession (Matthews, 1992;Walker and del Moral, 2003;Pratch and Walker, 2020;Rosero et al, 2021), we found a clear successional increase in superficial SOM and N t . Values were relatively high considering the limiting conditions for soil development in the study area (e.g., steep slopes with hard exposed metamorphic bedrock and low vegetation cover), although they remained below typical values reported in the superpáramo belt in Venezuela between 4,000 and 4,400 m asl (Malagón, 1982;Pérez, 1995).…”
Section: Soil Developmentsupporting
confidence: 93%
“…Vascular plants only became the dominant structural component of vegetation after one century of succession (see Figures 2, 3). A similar pattern was reported by Sklenář et al (2010) in volcanic sere in Cotopaxi, while Rosero et al (2021) found a relative dominance of bryophytes over lichens and vascular plants during the first 65 years of post-glacial succession in a vanishing glacier in Carihuairazo (both in Ecuador). In agreement with our 2nd prediction, plant species richness increased during the first one hundred years of succession, which paralleled the observed increase in SOM and plant cover.…”
Section: Patterns Of Vegetation Assemblysupporting
confidence: 83%
See 1 more Smart Citation
“…In the European Alps, for example, glaciers have lost 25-30% of their surface area over the past 60 years, and the rate of ice loss is accelerating rapidly-it has been 200-300% faster in the past two decades than 40 years ago [5][6][7], and similar rates of retreat have been measured in other areas of the world [8]. The biotic and abiotic consequences of glacier retreat have received increasing attention in recent years, with research focusing on the biotic colonization, the formation and evolution of soils along glacier forelands, and the geomorphological hazards related to deglacierization [9][10][11][12][13][14], as well as on the impacts of glacier retreat on meltwater availability and human wellbeing [15,16]. In this context, broad-scale, spatially explicit information on the dynamics of glacier retreat is essential to assess the ecological dynamics of biotic colonization across multiple regions and to develop adequate adaptation and mitigation strategies to reduce geomorphological risks and cope with meltwater scarcity in arid regions.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical alpine regions additional limiting factors include reduced plant protection from seasonal snow and particularly fast rates of highelevation warming and glacier retreat (Rabatel et al, 2013;Wang et al, 2016;Vuille et al, 2018). However, studies of the patterns and mechanisms of primary succession in glacier forefields are scarce in the alpine tropics (see Spence, 1989;Mizuno, 2005;Mizuno and Fujita, 2014;Suárez et al, 2015;Zimmer et al, 2018;Anthelme et al, 2021;Rosero et al, 2021), especially under the harsh conditions that occur in mountains where they are about to become extinct.…”
Section: Introductionmentioning
confidence: 99%